Exploration and Experimental Research on the Mechanism of Electromagnetic Driven Weft Insertion (Journal of Fiber Bioengineering and Informatics, 2019)
In view of the current situation that there exists big impact and friction between the gripper and theguide in the weft insertion mode of the existing gripper loom, this paper puts forward the idea ofthe electromagnetic-driven two-way weft insertion on gripper in order to improve the energy conversionefficiency, reduce the friction and mechanical vibration. Electromagnetic drive is used as the basic methodto study the projecting/braking of the shuttle, and it uses the principle of electromagnetic levitation asthe basic principle of the shuttle’s weft insertion. In this paper, a basic model of two-way insertion isestablished. After ANSYS simulation and experimental analysis, the speed of electromagnetic drivingcan reach 30 m/s. In the electromagnetic levitation stage, PWM modulator and DC power regulationwere respectively used to conduct the levitation control experiment. HW101 hall sensor was used tojudge the levitation state, and with the assistance of other Operational Amplifier, the requirements ofelectromagnetic levitation were completed.
Keywords: Gripper Loom; Weft Insertion; Electromagnetic Levitation; Shuttle Projecting.